Chitosan in the preservation of agricultural commodities - Bautista-Banos, Silvia; Romanazzi, Gianfranco; Jimenez-Aparicio, Antonio (Academic Press, 2016)
Chitosan in the Preservation of Agricultural Commodities presents a cohesive overview of research topics regarding the production and characterization of chitosan, the development of coatings and fi lms, its functional properties, and antimicrobial potential of this compound on economically important agricultural commodities. It includes the modes of action from a physiological, enzymatic, and molecular perspective, and evaluations of the activity of chitosan nanocomposites and nanoparticles in biological models. The first section deals with the chemical characteristics and functional properties of chitosan and new chitosan-based biomaterials intended for food preservation. The second section covers various aspects of the control achieved by chitosan on different microorganisms affecting various horticultural commodities, grains, and ornamentals, and its modes of action. The third section explores enzymatic and gene expression induction by chitosan application on fruit and vegetables; the fourth section offers insight on the use of chitosan nanocomposites in biological models associated with food conservation and control of microorganisms.